The value of non-working time incorporated in quality of life comparisons: The case of the US vs. the Netherlands - Ellen Verbakel; Thomas A. DiPrete (Luxembourg Income Study (LIS), 2007)
Comparisons of well-being across societies depend both on the amount of inequality at the national level and also on the national average level of well-being. Comparisons between the U.S. and western Europe show that inequality is greater in the U.S. but that average GDP per capita is also greater in the U.S., and most Americans have higher standards of living than do western Europeans at comparable locations in their national income distributions. What is less wellknown is that (depending on the country) much or all of this gap arises from differences in the level of working hours in the U.S. and in western Europe. Cross-national comparisons of wellbeing have typically relied on the methodology of generalized Lorenz curves (GLC), but this approach privileges disposable income and cash transfers while ignoring other aspects of welfare state and labor market structure that potentially affect the distribution of well-being in a society. We take an alternative approach that focuses on the value of time use and the different distributions of work and family time that are generated by each country's labor market and social welfare institutions. In this empirical exercise involving the U.S. and the Netherlands, we show that reasonable estimates of the contribution to well-being from non-market activities such as the raising of children or longer vacations can overturn claims in the literature that the U.S. offers greater well-being to more of its citizens than do western European countries.
Keywords: 330